Pemberdayaan Ekonomi Masyarakat Pesisir Ramah Lingkungan (Penelitian Di Belawan Kota Medan) - Mukidi Mukidi (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
AbstractNatural resources as the main supporters of national development need to be considered to meet the interests of current and future generations. Therefore, various policies have been issued to maintain the natural resources as capital to realize the welfare of the entire nation by keeping maintaining the carrying capacity and the function of the environment. However, until now there are still a lot of damage, pollution, and natural disasters due to the management of natural resources that excludes the sustainability of environmental functions. The condition is compounded by the decline of vegetation cover in protected areas, loss of mangrove ecosystems / coastal plants, the increasing destruction of watersheds, and loss of water resources and decreasing quality of river and sea water. The visible immediate impacts are such as droughts, floods and landslides in various areas that cause human casualties, damage / disrupt the functioning of infrastructure, and worsened access of clean water. Keywords: economic empowerment, friendly environment